A first large study of whole-exome sequencing (WES) in 489 patients with suspected rare genetic disorders at a tertiary centre in Malaysia - Lip Hen Moey; Go Hun Seo; Boon Eu Cheah; Wee Teik Keng; Hane Lee; Gaik Siew Ch’ng (Rare)
Introduction: Rare genetic disorders occur at a rate of 40–82 per 1000 live births worldwide. Identifying the molecular cause of rare genetic disorders is beneficial because it allows early diagnosis, facilitates treatment planning and provision of accurate genetic counselling. In Malaysia, it is estimated that 1.5–2 million (4–6 %) people from a population of 34 million suffer from rare disorders, most of which are genetic in origin. Tests offered to patients referred to genetic clinics in Malaysia include conventional karyotyping, Fragile X testing, metabolic screening and/or single gene testing. Chromosomal microarray analysis (CMA) and gene-panel testing are not routinely offered due to lack of laboratory resources. Hence, the majority of rare disease patients remain undiagnosed for many years. Whole exome sequencing (WES) is a comprehensive test that can detect not only many of the same large deletions and duplications as CMA, but also detect other genetic variants that are detected by gene panels. Therefore, WES is cost effective and fast becoming a routine clinical test worldwide for patients suspected to have rare genetic disorders. Method: This is a retrospective study conducted at a single genetic centre in Malaysia. From August 2020 to December 2021, proband-only WES was offered to patients suspected of having a genetic disorder after clinical evaluation by a clinical geneticist. WES was performed at a single reference laboratory in South Korea. Patient demographic information, clinical features, genetic test results were collected from the case notes for analysis. Results: A total of 489 patients underwent WES. Eighty-three percent (407/489) were paediatric patients. The majority of the patients presented with neurodevelopmental symptoms. WES identified the underlying genetic cause in 50 % (243/489, 95 % confidence interval (CI): 45 %-54 %) of the patients. A reanalysis of WES data, with or without additional phenotypic information, yielded a diagnosis for 17 of the 228 WES-negative patients, resulting in the final diagnostic yield of 53 % (260/489, 95 % CI: 49 %-58 %). Nine of these patients received dual molecular genetic diagnosis. Twenty one patients were diagnosed with a copy-number-variant (CNV). The inheritance patterns of the diagnosed disorders were 64 % autosomal dominant (171/268), 24 % autosomal recessive (65/268) and 12 % X-linked (32/268). 82 % (401/489) of the patients opted to receive secondary finding results, of which 5.5 % (22/401, 95 % CI: 3.6 %-8.2 %) had P/LP variants in genes associated with cardiovascular disorders (64 %, 14/22) or cancer (27 %, 6/22). Conclusion: This study demonstrated the high efficiency of WES in confirming rare genetic diagnoses among patients referred to a genetic clinic in Malaysia. Identifying resources to fund this test would be of utmost importance to achieve the aim of universal health care provision to people living with rare diseases, as stipulated in the 2019 United Nations political declaration.